Understanding block rotation of strike-slip fault zones: Paleomagnetic and structural approach - Hernandez Moreno, Catalina <1981> (Alma Mater Studiorum - Università di Bologna, 2015)
This thesis is focused on the paleomagnetic rotation pattern inside the deforming zone of strike-slip faults, and the kinematics and geodynamics describing it. The paleomagnetic investigation carried out along both the LOFZ and the fore-arc sliver (38º-42ºS, southern Chile) revealed an asymmetric rotation pattern. East of the LOFZ and adjacent to it, rotations are up to 170° clockwise (CW) and fade out ~10 km east of fault. West of the LOFZ at 42ºS (Chiloé Island) and around 39°S (Villarrica domain) systematic CCW rotations have been observed, while at 40°-41°S (Ranco-Osorno domain) and adjacent to the LOFZ CW rotations reach up to 136° before evolving to CCW rotations at ~30 km from the fault. These data suggest a directed relation with subduction interface plate coupling. Zones of high coupling yield to a wide deforming zone (~30 km) west of the LOFZ characterized by CW rotations. Low coupling implies a weak LOFZ and a fore-arc dominated by CCW rotations related to NW-sinistral fault kinematics. The rotation pattern is consistent with a quasi-continuous crust kinematics. However, it seems unlikely that the lower crust flux can control block rotation in the upper crust, considering the cold and thick fore-arc crust. I suggest that rotations are consequence of forces applied directly on both the block edges and along the main fault, within the upper crust. Farther south, at the Austral Andes (54°S) I measured the anisotropy of magnetic susceptibility (AMS) of 22 Upper Cretaceous to Upper Eocene sites from the Magallanes fold-thrust belt internal domains. The data document continuous compression from the Early Cretaceous until the Late Oligocene. AMS data also show that the tectonic inversion of Jurassic extensional faults during the Late Cretaceous compressive phase may have controlled the Cenozoic kinematic evolution of the Magallanes fold-thrust belt, yielding slip partitioning.